Caracterização de filme polissacarídico obtido de casca de MANDIOCA (Manihot esculenta) funcionalizado com óleo essencial de cravo-da-índia (Syzygium aromaticum) - Yuri Dias Oliveira Silveira (2018)
It's highlighted the generation of significant amounts of waste among the main issues related to strategies for sustainable agro-industrial development and production. Lignocellulosic residues are abundant, inexpensive and widely available. In the case of manioc (Manihot esculenta) and its residues, it is possible to convert them into products of interest to the industry itself, such as the extraction of biopolymers and the consequent development of biodegradable plastic packaging, in which case the starch is the substance of interest. The functionalization of such films with natural antimicrobial agents is shown to be promising since they can result in active packagings which aim to increase the shelf life of the products contained therein. The extracts were submitted to oxidative treatment with sodium hypochlorite (NaClO) and hydrogen peroxide (H2O2), both of which were used in this work. The extracts were extracted from cassava husks collected at the Central Market of the city of Belo Horizonte, MG. three concentrations: 2, 6 and 10% (v / v) to clarify the extracts obtained and consequently the resulting films. The extracts, both native and oxidized, were characterized in terms of color, monosaccharide profile, infrared spectroscopy reading and protein content. The films were prepared from the extracts, submitted to functionalization from the addition of 2 g of clove essential oil (Syzygium aromaticum) to their composition and tested against Stapylococcus aureus, Listeria monocytogenes and Salmonella Typhimurium. The extracts treated with 6% NaClO presented satisfactory results in relation to bleaching, resulting in lightcolored films with inhibition halos up to 11.87 ± 1.62 mm in diameter, water vapor permeability value of 0.14 ± 0.06 g.mm/m2.h.kPa and elongation at break of 48.01 ± 18.77%. The characteristics presented by the films are promising, but more studies are needed to improve their properties and the feasibility of their production